Applied statistics for engineers and physical scientists - Hogg, Robert V.; Ledolter, Johannes; Hogg Robert V. Engineering statistics (New York : Macmillan, 1992)
Rev. ed. of: Engineering statistics 1987.
Includes index.
Keywords: Engineering -- Statistical methods